Crop rotation - a double benefit - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Assistant Director of the Kenya Institute of Organic Farming describes the crop rotation techniques that they teach, and the need for a national certifying body in order to support organic farmers.